(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific and methodological support of sports activities in Olympic and professional sports is a set of measures aimed at improving the efficiency of athletes’ training, optimizing training processes, and ensuring competitiveness in the international arena. This is based on the integration of modern scientific achievements in the fields of sports, medicine, psychology, biomechanics, information technology, and more. The purpose of this article is to study and discuss the problem of scientific and methodological support for sports activities in Olympic and professional sports. Scientific and methodological support is a key factor in the development of Olympic and professional sports, as it allows for the optimization of the training process, increases the efficiency of athletes’ training, and improves their results. This analysis of recent research and publications enables us to identify the main components of scientific and methodological support for sports activities in Olympic and professional sports, including theoretical foundations and scientific research, the training process, medical and biological support, physiological and biochemical support, psychological support, and psycho-pedagogical support. The scientific and methodological support of sports activities in Olympic and professional sports is a crucial factor that determines the effectiveness of the educational and training processes of athletes and their competitiveness in the sports arena. The analysis of scientific sources has confirmed the importance of integrating modern methods that cover physiological, biomechanical, biomedical, psychological, and informational aspects of training. The use of the latest technologies, including video analysis, artificial intelligence, and sports analytics, contributes to the personalization of the training process and increases its effectiveness. Further development of scientific and methodological support for sports activities involves the integration of interdisciplinary research, technological innovations, and modern approaches to the training process. This will contribute not only to improving the performance of athletes but also to the overall development of sport as a social phenomenon.